2000
DOI: 10.1002/1097-0215(20000901)87:5<695::aid-ijc12>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Breaking tolerance to a tumor-associated viral superantigen as a basis for graft-versus-leukemia reactivity

Abstract: A major goal in tumor immunotherapy consists of breaking potential tumor‐specific T‐cell unresponsiveness (tolerance), which may explain tumor growth in cancer patients. We report that immunological tolerance to a tumor‐associated viral superantigen (SAg) is overcome in a mouse lymphoma model by transfer of allogeneic T cells expressing SAg‐reactive Vβ6 T‐cell receptor chains. Surprisingly, upon contact with SAg‐expressing lymphoma cells, Vβ6 T cells became activated rather than tolerized (as reported previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…While it is not specifically demonstrated that Mtv SAgs play a direct role in an autoimmune process, previous work has demonstrated that these molecules modulate immune responses in experimental murine models of cancer and infectious disease ( 40 ). In models of polyomavirus- and Esb-induced lymphoma, the presence of the Mtv7 SAg presents a selective disadvantage by eliminating a population of T cells that are critical for tumor immunity ( 45 47 ). On the other hand, SAgs from Mtv7 and Mtv29 activate T cells respectively required to support the development of neuropathogenesis during Plasmodium berghei ANKA infection and spontaneous B cell lymphomagenesis ( 48 50 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While it is not specifically demonstrated that Mtv SAgs play a direct role in an autoimmune process, previous work has demonstrated that these molecules modulate immune responses in experimental murine models of cancer and infectious disease ( 40 ). In models of polyomavirus- and Esb-induced lymphoma, the presence of the Mtv7 SAg presents a selective disadvantage by eliminating a population of T cells that are critical for tumor immunity ( 45 47 ). On the other hand, SAgs from Mtv7 and Mtv29 activate T cells respectively required to support the development of neuropathogenesis during Plasmodium berghei ANKA infection and spontaneous B cell lymphomagenesis ( 48 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, SAgs from Mtv7 and Mtv29 activate T cells respectively required to support the development of neuropathogenesis during Plasmodium berghei ANKA infection and spontaneous B cell lymphomagenesis ( 48 50 ). It was possible to detect the involvement of Mtv SAgs in these disorders because they delete or activate a single critical TCR Vβ specificity that recognizes a discrete MHC-restricted antigen, such as an immunodominant peptide derived from the PyV middle T protein ( 51 ) and Mtv7 -encoded SAgs for Esb and B cell lymphomagenesis ( 47 ). In contrast, there is little evidence to support a role for Mtv SAgs in mouse models of complex diseases where pathology can be driven by T cells bearing different combinations of Vβ specificities.…”
Section: Discussionmentioning
confidence: 99%
“…Viruses inserted into host cell DNA, in a state of chronic or latent genomic endosymbiosis, encode oncoproteins which interact with cellular proteins to increase viral replication rates [79]. Oncogenesis results from a destabilization of genomic endosymbiosis and involves specific immunological factors involved in the symbiosis [80] and other factors relating to the cell itself: interferons [81], defensins [82], protein kinases [83] and interleukins [84,85]. These viral oncoproteins behave as targeted growth factors [86,87].…”
Section: Viral Agents and Oncogenesismentioning
confidence: 99%
“…Genotyping for Mtv among several of the tumor-resistant RI strains revealed similarity to the parental DBA/2 strain except for the loss of a particular LTR that corresponded to the Mtv-7 provirus. It was further demonstrated that ESb tumor cells themselves express proviral Mtv-7 at both the mRNA and protein level (66). Instead of inducing anergy among the Sag-reactive cells, the ESb tumor-associated Mtv-7 -encoded Sag was demonstrated to induce activation of Sag-specific cytotoxic T lymphocytes.…”
Section: Introductionmentioning
confidence: 99%
“…TCR Vβ6 cells were demonstrated to facilitate specific killing of tumor cells expressing the endogenous Mtv-7 in vitro . Furthermore, treatment of tumor-bearing DBA/2 mice with TCR Vβ6 T cells from naïve B10.D2 mice led to a significant increase in survival and concurrent reduction in tumor growth (66). It is important to note that the reduction in tumor growth and delay in death lasted only 10 days, suggesting the potential and eventual loss of the TCR Vβ6 T cell population.…”
Section: Introductionmentioning
confidence: 99%